"Moderate" Minimum wages are likely to benefit workers after all: A general equilibrium view - López, Ramón (Estudios de Economía, 2016)
It is shown that long-held views on the links between minimum wages and human capital arising from on-the-job training are not in general valid in a general equilibrium context. Of the three propositions obtained from partial equilibrium models, namely that minimum wages cause (i) firms to reduce training, (ii) the fall of the average lifetime wage of workers that receive training, (iii) the decline of employment in industries that provide training, only the first hold while the other two are likely to be reversed. Moreover, it is also shown that capitalists are likely to carry more than the complete social cost of the minimum wage and that workers welfare increase.